TRANSGENDER ADAPTATION IN ACHIEVING THE SOCIAL ACCEPTABILITY IN PEMATANGSIANTAR - donny siburian (UIN Raden Mas Said Surakarta, 2023)
Abstract Society expected men to behave masculine and play a role like men, and women to behave like women (feminine), who are naturally oriented towards normal sexuality, namely crossing each other. The existence of transgender people who are present in society is perceived as deviant individuals. The purpose of this research is to see the form of community stereotypes towards transgender in Pematangsiantar City, as well as adaptation strategies carried out by transgender people who are accepted (acceptable) in society. This research method is a mix method with a tendency to analyze qualitative data supplemented by quantitative data. The result of this research shows that there are various negative stereotypes attached to transgender people in Pematangsiantar City. Therefore, the various endeavors or strategies of transgender people to adapt or adjust themselves to be accepted (acceptable) as themselves and members of society is a separate effort made by transgender people in the midst of society. This research can be a reference in dealing with social life that exists in the midst of society in dealing with social status as transgender. Keywords : Transgender; Adaptation; Stereotypes; Social; Acceptability.